VEGF suppresses T‐lymphocyte infiltration in the tumor microenvironment through inhibition of NF‐κB‐induced endothelial activation. Issue 1 (31st October 2014) - Huang, Hua; Langenkamp, Elise; Georganaki, Maria; Loskog, Angelica; Fuchs, Peder Fredlund; Dieterich, Lothar C.; Kreuger, Johan; Dimberg, Anna
Abstract : Antiangiogenic treatment targeting the vascular endothelial growth factor (VEGF) signaling pathway is in clinical use, but its effect on vascular function and the tumor microenvironment is poorly understood. Here, we investigate cross‐talk between VEGF and proinflammatory TNF‐α signaling in endothelial cells and its impact on leukocyte recruitment. We found that cotreatment with VEGF decreased TNF‐α‐induced Jurkat cell adhesion to human microvascular endothelial cells by 40%. This was associated with inhibition of TNF‐α‐mediated regulation of 86 genes, including 2 T‐lymphocyte‐attracting chemokines, CXCL10 and CXCL11 [TNF‐α concentration 1 ng/ml; 50% inhibition/inhibitory concentration (IC50 ) VEGF, 3 ng/ml]. Notably, VEGF directly suppressed TNF‐α‐induced gene expression through negative cross‐talk with the NF‐κB‐signaling pathway, leading to an early decrease in IFN regulatory factor 1 (IRF‐1) expression and reduced phosphorylation of signal transducer and activator of transcription 1 (p‐Stat1) at later times. Inhibition of VEGF signaling in B16 melanoma tumor‐bearing mice by sunitinib treatment resulted in up‐regulation of CXCL10 and CXCL11 in tumor vessels, accompanied by up to 18‐fold increased infiltration of CD3 + T‐lymphocytes in B16 tumors. Our results demonstrate a novel role of VEGF in negative regulation of NF‐κB signaling and endothelial activation in the tumor microenvironment and provide evidence that pharmacological inhibition of VEGF signaling enhances T‐lymphocyte recruitment through up‐regulation of chemokines CXCL10 and CXCL11.—Huang, H., Langenkamp, E., Georganaki, M., Loskog, A., Fuchs, P. F., Dieterich, L. C., Kreuger, J., Dimberg, A., VEGF suppresses T‐lymphocyte infiltration in the tumor microenvironment through inhibition of NF‐κB‐induced endothelial activation. FASEB J. 29, 227–238 (2015). www.fasebj.org